La integración regional a comienzos del siglo XXI : MERCOSUR y UNASUR (2011)
ABSTRACT: During the first half of the 20th century, they presented Integration projects in Latin America in the light of the concept of "Pan Americanism" and closely related to the emergence of The United States as world power. For the second half of century, after the creation of the Economic Commission for Latin America (CEPAL), there appeared projects that under the surname "Latin-American" (ALALC, ALADI), reflected the renovation of the intentions of integration. Nevertheless, difficulties reappeared for the regional community. Nowadays, two projects exist in process of formation to stand out: the Common Market of the South (MERCOSUR, in 1994), that has continued very in spite of the varied difficulties that appear him, understood many of these for his recent constitution. And it does little a new project arose: the Union of South American Nations, (UNASUR, in 2008), that alternates as offer of integration with the Alternative Bolivariana for the Peoples of Our America (ALBA, in 2004). These ambitious projects interact abreast to the many-colored political - ideological spectrum of the South American region. The aim is to do an analysis of both recent projects of integration bearing in mind the political - ideological context of the region and his repercussion in the process of formation of the same ones.